Assessment of Special Weapons and Tactics in the Province of Cavite: Basis for A Proposed Swat Operational Guidelines - Juanito A. Vergara Jr; John Paul R. Mallillin; Caezar P. Cabuhat (Future Science / FSH-PH Publications, 2026)
This study assessed the Special Weapons and Tactics (SWAT) units of the Philippine National Police in the Province of Cavite to serve as a basis for proposed operational guidelines. The study examined the personnel profile, perceptions regarding the selection process, facilities and equipment, and skills and capabilities, as well as the problems encountered and the solutions applied. A descriptive– correlational research design was employed using a researcher-made questionnaire validated by field experts. Data were collected from 105 SWAT personnel and analyzed using frequency, percentage, mean, Chi-square, and Spearman’s Rho. Findings revealed that while SWAT units are composed of capable and resilient personnel, several gaps remain in equipment, training, and administrative support. Most respondents possessed only a bachelor’s degree, and a large proportion had attended only one specialized training session, indicating limited opportunities for advanced tactical development. The results also showed that rank and age were the least influential criteria in selection, suggesting a shift toward merit-based recruitment focused on capability and readiness. Statistical tests indicated varying levels of relationships between profile variables, perceptions, problems, and solutions. Based on the findings, operational guidelines were proposed to address equipment procurement, training enhancement, personnel welfare, and administrative support. The study contributes to improving the readiness and effectiveness of SWAT units in the province.